Achievement of effective cardiopulmonary trauma surgical skills training throughout the incorporation of a low-cost and easy to implement pulsatile simulation model. Issue 5 (May 2021) - Ortiz, C.; Vela, J.; Contreras, C.; Ávila, R.; Inzunza, M.; Quezada, J.; Jarry, C.; Ramos, J.P.; Ottolino, P.; Varas, J.; Jarufe, N.; Achurra, P.
Highlights: Injury-related mortality accounts for 5 million deaths per year. Chest trauma mortality rate is the second-highest after head-injury. There is concern regarding the preparedness of general surgery graduates to manage thoracic trauma cases. Simulation based training emerges as a solution, however high costs and low availability of simulation models often preclude the training to happen. We tested the effectiveness of incorporating a low-cost and easy to implement blended ex vivo tissue-based simulation model. The model proved to be an effective training and assessment tool for advanced surgical skills in cardiothoracic trauma. Abstract: Objectives: . In the last decade, concern regarding the preparedness of general surgery graduates to effectively manage thoracic trauma cases has been raised. However, due to limited availability and elevated costs, access to cardiopulmonary trauma simulation models is limited. This article describes our experience implementing a low-cost blended ex vivo tissue-based simulation model using animal by-products that incorporates pump perfusion and ventilation. Design: . Firstly, for validation purposes 8 junior residents, 8 recently graduated general surgeons, and 3 cardiothoracic surgery attendings from Pontificia Universidad Católica de Chile Clinical Hospital were recruited. Proficiency in performing a pulmonary tractotomy and a myocardial injury repair was assessed with global and specific rating scales. Secondly, to evaluate the effectiveness of the model as a learning tool, 16 general surgery residents from different programs across the country were recruited receiving intensive, personalized training on the models. Proficiency was measured before and after the training. Results: . For the validation phase, significant differences among groups according to the previous level of expertise were shown, and therefore construct validity was established. The results of the second phase showed a significant overall improvement in participant's performance. Conclusion: . Effective training and assessment for advanced surgical skills in cardiothoracic trauma can be achieved using a low-cost pulsatile simulation model.